Village Consultative Body in the Perspective of Village Autonomy in Tenga Village, Tenga District, South Minahasa Regency - Abdul R. Dilapanga,; Jeane Mantiri,; Lefran Lembong,; Yohanes Burdam,; Fonny Rewah,; Henry Lumenta, (Technium Social Sciences Journal, 2024)
This research aims to find out, analyze and describe the Village Consultative Body in the Village Autonomy Perspective in Tenga Village, Tenga District, South Minahasa Regency. This method uses descriptive qualitative research, the number of informants is 4 people with data collection techniques, namely observation, interviews and documentation, with analytical techniques data, drawing conclusions. The research results show that the implementation of the functions of the Village Consultative Body has not been implemented optimally. This is shown by the opinion of the public who consider that the Village Consultative Body has not carried out its functions optimally, starting from implementing the function of establishing village regulations, accommodating and channeling community aspirations to the stage of monitoring the implementation of Village regulations, so that there are community aspirations that are accommodated and channeled by the Village Consultative Body are not yet representativeer.